2014
DOI: 10.1007/s40121-014-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Evaluation of the 10-Valent Pneumococcal Non-typeable Haemophilus influenzae Protein D Conjugate Vaccine and 13-Valent Pneumococcal Vaccine in Japanese Children

Abstract: IntroductionDiseases caused by Streptococcus pneumoniae represent a major public health problem. The purpose of this study was to compare, in the Japanese context, the projected health benefits, costs and cost-effectiveness of the latest generation of pneumococcal conjugate vaccines which may provide important insight into the potential public health impact of interventions in the context of local disease-specific epidemiology.MethodsA Markov model was used to compare two vaccination strategies which involve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 40 publications
6
54
0
Order By: Relevance
“…PHiD-CV 2+1 was predicted to be dominant over PCV13 2+1. This dominance is in line with various other cost-effectiveness analyses, from Malaysia [ 10 ], Japan [ 57 ], the Philippines [ 27 ], Turkey [ 58 ], Europe [ 20 , 59 61 ], Canada [ 20 ] and Peru [ 53 ]. However, some studies have predicted the reverse: that PCV13 would be dominant over PHiD-CV (Malaysia and Hong Kong [ 11 ], Colombia [ 62 ], Europe [ 63 ] and Canada [ 64 ]) or more cost-effective than PHiD-CV (Peru [ 65 ]).…”
Section: Discussionsupporting
confidence: 82%
“…PHiD-CV 2+1 was predicted to be dominant over PCV13 2+1. This dominance is in line with various other cost-effectiveness analyses, from Malaysia [ 10 ], Japan [ 57 ], the Philippines [ 27 ], Turkey [ 58 ], Europe [ 20 , 59 61 ], Canada [ 20 ] and Peru [ 53 ]. However, some studies have predicted the reverse: that PCV13 would be dominant over PHiD-CV (Malaysia and Hong Kong [ 11 ], Colombia [ 62 ], Europe [ 63 ] and Canada [ 64 ]) or more cost-effective than PHiD-CV (Peru [ 65 ]).…”
Section: Discussionsupporting
confidence: 82%
“…A recent publication by Shiragami et al. (2014) 26 addressed the comparison of PHiD-CV 3+1 and PCV-13 3+1 in the context of a pediatric NIP in Japan over an analytical time horizon of 5 y. The model projected that vaccination with PHiD-CV would result in total cost savings of 16 million or 33 million USD from the provider and societal perspectives, with additional 433 QALYs gained compared with PCV-13.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In Japan, vaccination with PHiD-CV was also estimated to be cost-saving compared with PCV-13, from the healthcare provider and societal perspectives. 26 A review of 15 cost-effectiveness studies on PCV published between 2002 and 2006 found that PCV vaccination could generally be considered attractive in developed countries, although the results varied considerably between studies. 27 Factors contributing to the variation in results included differences in assumptions about vaccine efficacy parameters and disease incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, previous studies often estimate direct effects for each vaccine based on clinical trial efficacy data, adjusted by local PCV10 or PCV13 serotype coverage [64][65][66][67]. Alternatively, studies estimate the same efficacy for the common vaccine-type serotypes and assume PCV10 provides crossprotection for serotypes 6A and 19A [68][69][70], serotypes only contained in PCV13. However, these approaches are limited by outdated assumptions around serotype replacement and cross protection and create challenges when comparing across economic evaluations because of differences in the literature from which efficacy assumptions are drawn [71,72].…”
Section: Discussionmentioning
confidence: 99%